Comparing the bioavailability properties of bee pollen and bee bread using an in vitro digestive system - Aylanc, Volkan (2022)
The consumption of natural products has increased significantly due to the idea that whether improving nutrition, improves health, general well-being and reduces the risk of developing certain diseases. Bee products, in special bee pollen and bee bread, have demonstrated several nutritional and bioactive properties, which make them functional foods par excellence. Both bee pollen and bee bread are natural products rich in lipid, protein, carbohydrates as well as minor components such as phenolic compounds. Most of the bioactive properties are attributed to the powerful antioxidant and antiradical activity demonstrated by phenolic compounds. Nevertheless, bioactive claims are made without taking into consideration the further modifications to which phenolic compounds are subjected in the gastrointestinal tract. To determine and reveal the physicochemical parameter and the mechanisms of action of bioactive compounds in bee pollen and bee bread in the gastrointestinal tract, as well as the release of bioactive compounds from these bee products, determination of bioavailability properties and understanding their fate in the organism is crucial. In this context, the purpose of the present work was to compare the bioavailability properties of bee pollen and bee bread using an in vitro digestive system, as well as the determination of the nutritional parameters. The research was based on a series of tasks that started with the collection of bee pollen and bee bread followed by the determination of physicochemical properties like total lipid, protein, soluble sugar, total carbohydrates content and energetic value. The second step was to determine how the bioactive compounds in bee pollen and bee bread are affected in each phase of the in vitro digestive system and their bioaccessibility score and stability. Finally, the changes in their antioxidant capacity were determined. The study has shown that bee pollen and bee bread have different nutritional properties depending on their botanical origin. The results revealed that both bee products are rich sources of lipids, proteins and sugars, with high values in total carbohydrate and energy. The findings indicated a significant reduction in phenolic content in both bee pollen and bee bread samples at the end of gastrointestinal digestion compared to raw samples, and this was reflected in a decrease in their antioxidant capacity. Besides, the bioaccessibility scores for total phenolic content were calculated on average 31% and 38% for bee pollen and bee bread, respectively, whereas the bioaccessibilityscore for total flavonoid content averaged 25% (bee pollen) and 35% (bee bread). The results showed that both bee products are highly affected by in vitro digestion. In conclusion, this study clearly show that bee bread is either more accessible and richer in bioactive compound content compared to bee pollen, and both bee products have strong potential for widespread use in the food industry because of their rich macro and micronutrient content.